The Humanistic Values of the Permule Traditional Ceremony in Cikupa Village, Lumbung - Ciamis - Hidayat, Agung; Wijayanti, Yeni; Nurholis, Egi (Universitas Galuh, 2025)
The traditional Permule ceremony is held once a year when rice planting begins. The aim of this research is to determine the series of Permule Traditional Ceremony processions in Cikupa Village and the humanist values of the Permule Traditional Ceremony in Cikupa Village. The research method used is qualitative with data collection techniques in the form of observation, interviews and documentation. The results of this research are: (1) The Permule Traditional Ceremony procession series was carried out from the preparation stage with collecting funds, announcements/bewara, making offerings/offerings and preparing materials. Next, the opening ceremony took the form of everything, the process of planting rice trees and tawasul as well as prayer. The final stage of closing is eating together. (2) the humanist values in the Permule Traditional Ceremony are divided into 6, including: the value of respecting other people's opinions (freedom to express opinions), cooperation, sacrificial relationships, caring for other people, mutual help and the value of solidarity.